Private equity in Germany: the impact of debt and equity market conditions on the exit choice of private equity funds between 2000 and 2015 - Borrelli, Michele (2020)
Private equity funds face an essential decision, when it comes to the divestment choice of a portfolio company. Using a sample of 237 private equity transactions in Germany between 2000 and 2015, I observe that private equity funds take advantage of windows of opportunity being more likely to exit through an initial public offering (IPO) during ‘hot’ equity markets. Furthermore, secondary buyouts might be more resilient to rising interest rates rather than trade sales or IPOs. Due to the presence of more private equity capital in the market, funds tend to overpay for their targets, thereby, significantly increasing the volume of secondary buyouts.